Beneficial Effects of Red Wine Polyphenols on Human Health: Comprehensive Review - Ivana Buljeta; Anita Pichler; Josip Šimunović; Mirela Kopjar (Current Issues in Molecular Biology, 2023)
Polyphenols are secondary plant metabolites synthesized during the development of the grape berry as a response to stress conditions. They are important constituents in red wines that contribute to the sensory properties and antioxidant activity of wines. Due to the development of highly sophisticated analytical devices, it is now possible to characterize the structure of highly polymerized polyphenols and obtain a full polyphenol profile of red wines. Red wine polyphenols include the ones present in grapes as well as new polyphenol products formed during the winemaking process. Among them, the most important groups and their representatives are flavanols (catechin), stilbenes (trans-resveratrol), flavonols (quercetin) and hydroxybenzoic acids (gallic acid). It is known that polyphenols exhibit beneficial effects on human health, such as anti-inflammatory, anticarcinogenic and cardio-protective effects. Many studies have been conducted on the health effects of red wine polyphenols in cancer chemopreventive activities, neuroprotective effects and impact on cardiovascular diseases, gut microbiota in humans, etc. This review will provide major scientific findings on the impact of red wine polyphenols on human health as well as a review of polyphenols present in red wines and their main features.